(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Ayurveda is one of the most renowned traditional systems of medicine that has survived and flourished from ages till date. There are many avenues still to be explored by the researchers, practitioners and experts in the field who carry the responsibility of keeping the traditional systems of medicine alive and contributing to their growth in the future. Panchakarma is a fivefold treatment modality in Ayurveda used for detoxification of the body in preventive, curative as well as rejuvenative aspect. It includes Vamana (emesis), Virechana (purgation), Nirooha vasti (decoction enema), Nasya (instillation of medicine through nostrils), and Anuvasana vasti (oil enema). Kashyapa Samhita is a renowned book in Ayurveda especially in the field of Kaumarabritya. It elaborates Panchakarma procedures along with its indications, contraindications and doses for children. It contains many points explained in Brihat trayi along with some unique contributions in the field of Panchakarma. The present article reviews the original text and critically analyses the contribution of Kashyapa Samhita in the field of Panchakarma.